Augustine of Hippo as Doctor Pacis: Studies on Peace in the Contemporary World Vol. 2 Agustín de Hipona como Doctor Pacis: Estudios sobre la paz en el mundo contemporáneo Vol. 2 - Anthony Dupont (Editorial Uniagustiniana, 2019)
Debate is ongoing about Augustine's political philosophy, and more particularly about his views on the relations between Church and State. This volume brings together a number of contributions that examine Augustine's theoretical views on the subject. Augustine assumed his responsibilities as a theologian and Church leader: the truth of the faith and the unity of the Church could not be compromised. He did not hesitate to appeal to the civil authorities in the pursuit of this goal. In fact, he even ventured to deploy the civil authority, the emperor, against an ecclesiastical authority such as Pope Zosimus. This appeal to the secular arm of power was inspired on the one hand by Augustine's concern for the preservation of order and peace, and on the other by his faith in the rights of truth. Yet this aspiration of Augustine's was not absolute either. He rejected the idea that humans should be converted forcibly, against their will. He also condemned anything that compromised the physical integrity of human beings. In short, Augustine also recognised the value of the political system. This served to safeguard the good ends of earthly life, i.e. peace and justice. But Augustine believed this earthly peace and justice were reflections of the heavenly peace and justice, which are the foundation of earthly order and stability.